PENGELOLAAN DANA DESA UNTUK MENINGKATKAN KESEJAHTERAAN RAKYAT DI DESA PONGGOK KECAMATAN POLANHARJO KABUPATEN KLATEN - Maria Ulpa; Aos Kuswandi (Governance, 2023)
Ponggok Villagemanaged to utilize village funds to improve the welfare of its citizens. The purpose of this article is to describe and analyze the Village Fund Management Strategy and to examine the efforts of the Village Government in managing village funds for the welfare of the people. The method used in this study is descriptive qualitative to the object under study through secondary data collected. The results showed that successful management of village funds through the formation of Village Owned Enterprises able to improve people's welfare. Village Governments use transparency, accountability and participatory principles in village fund governance and continue to explore the potential in the village to improve people's welfare.